Transcriptional alteration of NF-κB-associated long noncoding RNAs in the stomach of Helicobacter pylori-infected and non-infected patients - Ghanbarian, Marzieh; Bakhtiari, Ronak; Mirbagheri, Seyedeh Zohre; Rezaei, Fatemeh; Rahimi Foroushani, Abbas; Alebouyeh, Masoud (The Journal of Infection in Developing Countries, 2023)
Introduction: Helicobacter pylori could colonize the gastric mucosa and cause gastritis, ulcers and cancer. Numerous virulence factors have been identified in this bacterium that play important roles in promoting gastric disorders. Although the interaction of long noncoding RNAs (lncRNAs) with transcription, processing, and translation of genes associated with different diseases are described, their interaction with the inflammatory genes and H. pylori infection in the gastric tissue is not well known. This study compared changes in common NF-κB-regulatory lncRNAs in the gastric tissue of H. pylori-infected and non-infected patients with gastritis. Moreover, a link between the virulence entity of the strains and the transcriptional changes was analyzed. Methodology: Two groups of infected and non-infected patients with chronic gastritis were included in the study. Genotyping of the H. pylori strains was done by PCR and relative changes in the expression of NF-κB and regulatory lncRNAs, lincRNA-p21, MALAT1, NKILA, were measured by relative quantitative real time-PCR. Results: Transcriptional levels of MALAT1, lincRNA-p21, and NKILA genes decreased in the infected patients compared with the non-infected patients, which was significantly linked with increased NF-κB gene expression. Our results showed that a hypervirulent strain of H. pylori with oipA“on”/HP-NAP+/iceA1+/iceA2+/vacA s1m1/s1m2+/cagA+ genotype can promote a higher level of NF-κB transcription in the inflamed tissue. Conclusions: H. pylori infection could promote down-regulation of lincRNA-p21, MALAT1 and NKILA in the infected gastric tissue in correlation with NF-κB upregulation. More detailed studies are needed to show a link between the virulence genes and their impact on the regulation of lncRNAs in the stomach.